Neonatal congenital myotonic dystrophy with DMPK gene expansion: clinical features and short-term outcomes - Zhao, Qian; Wang, Shupeng; Wang, Yang; Ding, Shenggang (Frontiers in Pediatrics, 2026)
ObjectiveTo investigate the clinical manifestations, diagnosis and treatment, and DMPK gene mutations in neonates with congenital myotonic dystrophy (CDM).MethodsA retrospective analysis was conducted on the clinical data of four neonates diagnosed with CDM and admitted to the Department of Neonatology at the First Affiliated Hospital of Anhui Medical University between January 2023 and December 2024.ResultsAmong the four cases, three were preterm and one was full-term. Polyhydramnios was noted in the pregnancies of all three preterm infants, and all mothers reported reduced fetal movement. Three preterm infants experienced birth asphyxia. All neonates presented with hypotonia to varying degrees—floppy limbs in preterm infants and marked hypotonia in the full-term infant. All four developed neonatal respiratory failure. Three preterm infants died during the neonatal period, whereas the full-term infant survived following successful weaning and oral feeding. Genetic testing revealed abnormal expansion of (CTG)n trinucleotide repeats in the DMPK gene in all cases, inherited maternally.ConclusionCDM should be considered in neonates presenting with unexplained birth asphyxia, hypotonia, and feeding or respiratory difficulties, especially when accompanied by maternal polyhydramnios and reduced fetal movement. Genetic testing enables early diagnosis and intervention.